OPTIMALISASI PENGGUNAAN INPUT USAHATANI BAWANG MERAH DI DESA SUNGAI GERINGGING KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR PROPINSI RIAU - Sri Ayu Kurniati; Darus (DINAMIKA PERTANIAN, 2018)
ABSTRACT Shallots are a strategic commodity but still require attention in the use of optimal inputs to achieve maximum results. All farm inputs are still limited in number while high production is highly expected by farmers. The purpose of this study was to determine the use of inputs, analyze the use of inputs in order to achieve optimal conditions and analyze the effect of input price changes on the optimal solution on red onion farming in Sungai Geringging Village, Kampar Kiri District, Kampar Regency. Descriptive qualitative and quantitative analysis methods using Linear Programming. The results of input use research state that the area of the land is narrow that is an average of 0.25 hectares, the seeds are superior but the number of uses is still below standard, more use of labor outside the family, dominant farmers use inorganic fertilizers, use pesticides to repel pests and work equipment simple one. The use of farming inputs is not optimal so that the reduction or addition of input availability will not affect the total profit in optimal conditions. The effect of changes when an input price increases and decreases by 3.25 percent does not show a difference when compared to the initial optimal conditions. Keywords: Optimization, Input, Shallot, Linear Programming, LINDO